GIS based novel hybrid computational intelligence models for mapping landslide susceptibility: A case study at Da Lat City, Vietnam - Nguyen V.-T.; Tran T.H.; Ha N.A.; Ngo V.L.; Nadhir A.-A.; Tran V.P.; Nguyen H.D.; Malek M.A.; Amini A.; Prakash I.; Ho L.S.; Pham B.T. (MDPI, 2023)
artificial intelligence; computer simulation; damage mechanics; disaster management; GIS; land use planning; landslide; mapping; NDVI; weathering; Da Lat; Viet Nam